EVALUASI PELAKSANAAN KEWAJIBAN KEPALA DESA SEBAGAI FASILITATOR DALAM MEMBERDAYAKAN MASYARAKAT DESA DI DESA LUBUK BENDAHARA TIMUR KECAMATAN ROKAN IV KOTO KABUPATEN ROKAN HULU - Afrizal, Afrizal; Ali, Zaini (UIR PRESS, 2016)
Government Regulation No. 72 Year 2005 on the village of Article 15 Paragraph 1 of the obligations of the village chief said that one of the aforementioned article on the letter n said that the Village Head has a duty to empower people and institutions in the village. The aim of the study is to examine the results of implementation of Obligations Village Head In Empowering Village community and to determine the factors inhibiting the Implementation of Obligations Village Head In Empowering villagers in the village of Lubuk Bendahara Timur , District Rokan IV Koto, Rokan Hulu, the author uses the theory of evaluation according to Ndraha with indicator of community empowerment, empowerment of civil society as a partner, the welfare of society. The type of research is quantitative descriptive as well as the study population is the village chief Lubuk Bendahara Timur , the Village , Institutional village, and heads of family are determined by census technique and purposive sampling, kind of collection of data used are primary data and secondary data, techniques in data collection using questionnaires, interviews and observations, then the data were analyzed descriptively using quantitative descriptive method based on the analysis of meaning Evaluation of obligation village chief in empowering Village Community in the village of Lubuk Bendahara Timur District of Rokan IV Koto Rokan Hulu assessed Enough to Succeed, It is expected that the Government the village of Lubuk Bendahara Timur to further improve community development activities village so that people-power and welfare level increased.